THE EFFECT OF CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL DISTRESS: THE MODERATING ROLE OF PROFITABILITY - Ghaniya Azzahra Zen; Hero Priono (JAT : Journal Of Accounting and Tax, 2026)
This study examines the effects of independent commissioners, audit committee, and Corporate Social Responsibility on financial distress, with profitability as a moderating variable. The study focuses on property and real estate companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach, secondary data were collected from annual reports, financial statements, and sustainability reports. The sample consisted of 52 companies selected through purposive sampling, resulting in 156 observations. Financial distress was measured using the Altman Z-Score and analyzed using binary logistic regression with interaction terms. The results show that audit committee and CSR significantly reduce financial distress, whereas independent commissioners have no significant effect. Profitability moderates the relationships between independent commissioners and financial distress as well as between CSR and financial distress, but does not moderate the relationship between audit committee and financial distress. These findings indicate that effective monitoring through audit committees and stronger CSR disclosure contribute to reducing financial distress risk, while profitability enhances the effectiveness of certain governance and sustainability mechanisms. This study contributes to the financial distress literature and provides implications for managers, investors, creditors, and regulators in managing financial distress risk within the property and real estate sector.